Maternal urinary phthalates and sex-specific placental mRNA levels in an urban birth cohort - Jennifer J. Adibi; Jessie P. Buckley; Myoung Keun Lee; Paige L. Williams; Allan C. Just; Yaqi Zhao; Hari K. Bhat; Robin M. Whyatt (BMC, 2017)
Abstract Background Prenatal urinary concentrations of phthalates in women participants in an urban birth cohort were associated with outcomes in their children related to neurodevelopment, autoimmune disease risk, and fat mass at 3,5,7, and 8 years of life. Placental biomarkers and outcomes at birth may offer biologic insight into these associations. This is the first study to address these associations with candidate genes from the phthalate and placenta literature, accounting for sex differences, and using absolute quantitation methods for mRNA levels. Methods We measured candidate mRNAs in 180 placentas sampled at birth (HSD17B1, AHR, CGA, CYP19A1, SLC27A4, PTGS2, PPARG, CYP11A1) by quantitative PCR and an absolute standard curve. We estimated associations of loge mRNA with quartiles of urinary phthalate monoesters using linear mixed models. Phthalate metabolites (N = 358) and mRNAs (N = 180) were transformed to a z-score and modeled as independent, correlated vectors in relation to large for gestational age (LGA) and gestational diabetes mellitus (GDM). Results CGA was associated with 4 out of 6 urinary phthalates. CGA was 2.0 loge units lower at the 3rd vs. 1st quartile of mono-n-butyl phthalate (MnBP) (95% confidence interval (CI): −3.5, −0.5) in male placentas, but 0.6 loge units higher (95% CI: −0.8, 1.9) in female placentas (sex interaction p = 0.01). There was an inverse association of MnBP with PPARG in male placentas (−1.1 loge units at highest vs. lowest quartile, 95% CI: −2.0, −0.1). CY19A1, CYP11A1, CGA were associated with one or more of the following in a sex-specific manner: monobenzyl phthalate (MBzP), MnBP, mono-iso-butyl phthalate (MiBP). These 3 mRNAs were lower by 1.4-fold (95% CI: −2.4, -1.0) in male GDM placentas vs. female and non-GDM placentas (p-value for interaction = 0.04). The metabolites MnBP/MiBP were 16% higher (95% CI: 0, 22) in GDM pregnancies. Conclusions Prenatal concentrations of certain phthalates and outcomes at birth were modestly associated with molecular changes in fetal placental tissue during pregnancy. Associations were stronger in male vs. female placentas, and associations with MnBP and MiBP were stronger than other metabolites. Placental mRNAs are being pursued further as potential mediators of exposure-induced risks to the health of the child.